Analisis Perkembangan Dan Daya Dukung WilayahUntuk Evaluasi Penentuan Pusat PemerintahanKabupaten Madiun Jawa Timur 2005 - 2014 - Triawa, Triawan; , Drs. M. Musiyam, M.TP; , Dra. Umrotun, M.Si (2016)
Given the importance of the role and functions of the center of government in supporting economic growth and development. This research aims to: Analyze the spatial variation of the level of development and the carrying capacity of the area in Madiun District in 2005-2014 as well as determine and evaluate the most suitable sub-district as Capital region in Madiun District. The used approaching methods are Spatial Approaching and Complex Region. The used method is summative evaluation. The development of Madiun District was analyzed by three main indicators: (1) economy and demography; (2) accessibility, transport and communication; and (3) socio-economic services. While carrying capacity are analyzed through the analysis of protected areas and land capacity analysis. The results showed that the development is quite good in Madiun District, where the area was classified as advanced in 2004 only three sub-district while there are six sub-district classed as developed and underdeveloped. However, in 2009 the region entered the advanced classification become four sub-district; five sub-district classed as developed; and six sub-district were classed as underdeveloped. Developments in Madiun District continued until 2014 there were only three sub-district with underdeveloped classification; eight sub-district with developed classification and four sub-district with advanced classification. The analysis of protected area generate region that has support for the urban development of the sub-district only Kare and Saradan with potential classification, while the land capacity analysis shows that all regions in Madiun District have potential support to urban development, except the Sub-district Dagangan, Gemarang and Kare. Based on the research results, the region of the most suitable as the Capital District in Madiun is Sub-district Dolopo. Despite that the Sub-district Mejayan chosen as capital in 2010, when the development of the region is classified as developed from year 2005 to 2014.Given the critical role and functions of the central government, the government should accelerate the development, especially in Sub-district Mejayan so that the move of center of the government to accelerate economic growth and development can be realized, as well as capable of being a center of growth and stimulate the development of the surrounding area.